Determinants of changes in pulmonary artery pressure in patients with severe aortic stenosis treated by transcatheter aortic valve implantation. Issue 2 (4th March 2021) - Strachinaru, Mihai; Ren, Ben; van Dalen, Bas M.; Van Mieghem, Nicolas; De Jaegere, Peter P. T.; van Gils, Lennart; Galema, Tjebbe W.; Geleijnse, Marcel L.
Abstract: Background: Elevated pulmonary artery pressure (PAP) in patients with severe aortic stenosis (AS) is a strong predictor of adverse prognosis. This study sought to assess the relation between PAP and clinical and echocardiographic parameters in elderly patients with severe AS, as well as to identify the determinants of the change in PAP after transcatheter aortic valve implantation (TAVI). Methods: The study included 170 subjects (age 81 ± 7 years, 45% men) with symptomatic severe AS who were treated by TAVI. They underwent a clinical evaluation and a transthoracic echocardiography before the TAVI procedure and 6 months after. Results: In a multivariable analysis, the independent predictors for baseline PAP were the body mass index (BMI) ( β  = 0.21, p  = .006), COPD GOLD class ( β  = 0.20; p  = .009), the E / e ′ ratio ( β  = 0.20; p  = .02) and the degree of aortic regurgitation ( β  = 0.20; p  = .01). After TAVI, there was significantly less (51% vs. 29%, p <.0001) pulmonary hypertension, defined as a tricuspid regurgitation velocity ≥2.8 m/s. The baseline variables related to an improvement in PAP were the tricuspid regurgitation velocity ( p  = .0001) and the E / e ′ ( p  = .005). From the parameters potentially modified with TAVI, the only independent predictor of PAP variation was the change in the E / e ′ ratio ( β  = 0.23; p  = .01). Conclusions: Independent predictors for baseline PAP in elderly patients with symptomatic AS were the BMI, GOLD class, the aortic regurgitation and the E / e ′ ratio. The baseline predictors for a change in PAP 6 months after TAVI were the baseline PAP and E / e ′, with only the change in the E / e ′ ratio being correlated to the change in PAP.